Pros and Cons Tourism Development in Komodo National Park, Indonesia - Choirisa, Septi Fahmi (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
The rapid tourism development of Komodo National Park (KNP) as part of the restructuring of the Labuan Bajo strategic tourism area in Indonesia has aroused concerns. The conservation area within the biosphere reserve plays a pivotal role in preserving the natural environment and essential resources necessary for the survival and habitat of Komodo dragons. The global dissemination of social, economic, environmental, and conservation issues through the media has garnered significant attention. This study examines the local perspectives on tourism development in KNP. A qualitative method was employed through in-depth interviews with stakeholders such as local communities, government, NGOs, educators, indigenous, entrepreneurs, and travel agencies. This study found that destination development has altered their socioeconomic which is perceived as benefits and drawbacks. This study contributes to tourism development literature. This research suggests that KNP management, government, and stakeholders involved in the project planning need to consider local involvement to facilitate sustainable outcomes.